Targeted re-sequencing on 1p22 among non-syndromic orofacial clefts from Han Chinese population - Li, Mu-Jia; Shi, Jia-Yu; Zhang, Bi-He; Chen, Qian-Ming; Shi, Bing; Jia, Zhong-Lin (Frontiers in Genetics, 2022)
Rs560426 at 1p22 was proved to be associated with NSCL/P (non-syndromic cleft lip with or without the palate) in several populations, including Han Chinese population. Here, we conducted a deep sequencing around rs560426 to locate more susceptibility variants in this region. In total, 2,293 NSCL/P cases and 3,235 normal controls were recruited. After sequencing, association analysis was performed. Western blot, RT-qPCR, HE, immunofluorescence staining, and RNA sequencing were conducted for functional analyses of the selected variants. Association analysis indicated that rs77179923 was the only SNP associated with NSCLP specifically (p = 4.70E-04, OR = 1.84), and rs12071152 was uniquely associated with LCLO (p = 4.00E-04, OR = 1.30, 95%CI: 1.12–1.51). Moreover, de novo harmful rare variant NM_004815.3, NP_004806.3; c.1652G>C, p.R551T in ARHGAP29 resulted in a decreased expression level of ARHGAP29, which in turn affected NSCL/P-related biological processes; however, no overt cleft palate (CP) phenotype was observed. In conclusion, rs12071152 was a new susceptible variant, which is specifically associated with LCLO among the Han Chinese population. Allele A of it could increase the risk of having a cleft baby. Rs77179923 and rare variant NM_004815.3, NP_004806.3; c.1652G>C, p.R551T at 1p22 were both associated with NSCLP among the Han Chinese population. However, this missense variation contributes to no overt CP phenotype due to dosage insufficiency or compensation from other genes.